Pengaruh Tingkat Inflasi, Bi-7 Days Repo Rate, dan Nilai Tukar Usd/Kurs terhadap Indeks Harga Saham Gabungan - Andhani, Destian; Wahidah, Nur Rachmah; Simangunsong, Ria Rosalia (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2023)
The aim of the research is regarding the Influence of the Inflation Rate, Bi-7 Days Repo Rate, and USD/Exchange Rate on the IHSG Composite Stock Price Index on the Indonesian Stock Exchange in 2017-2021. The Indonesian Stock Exchange (BEI) has a composite index known as the Composite Stock Price Index (IHSG). When the JCI shows an increase, it means that the Indonesian economy is in good condition and the opposite applies. The JCI movement is certainly influenced by several macroeconomic factors, therefore this research aims to determine the development of the Inflation level, BI-7 days Reverse Repo Rate, USD/Exchange Rate, IHSG and determine the significance of the influence of the Inflation variable, BI-7 days Reverse Repo Rate, and USD Exchange Rate both partially and simultaneously against IHSG on BEI. The research method used in this research is the multiple linear regression analysis method which is processed using SPSS 25. This type of research is descriptive with qualitative analysis. Based on the research results, it is concluded that based on the results of the F test, the inflation rate, BI-7DRR, and USD exchange rate simultaneously have a significant effect on the IHSG. The results of research using the t-test concluded that the inflation rate had no and insignificant influence on the IHSG, while the BI-7DRR variable had a positive and significant influence on the IHSG, and the USD Exchange Rate had a negative and significant influence on the IHSG. ABSTRAK  Tujuan dari penelitian ini untuk melihat pengaruh Tingkat Inflasi, Bi-7 Days Repo Rate, dan Nilai Tukar Usd/Kurs terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia Tahun 2017-2021. Bursa Efek Indonesia (BEI) memiliki indeks gabungan yang dikenal dengan Indeks Harga Saham Gabungan (IHSG). Di saat IHSG menunjukkan peningkatan berarti perekonomian Indonesia berada dalam keadaan yang baik dan berlaku sebaliknya. Pergerakan IHSG tentu dipengaruhi oleh beberapa faktor makroekonomi oleh karenanya penelitian ini bertujuan untuk mengetahui perkembangan tingkat Inflasi, BI-7 days Reverse Repo Rate, Nilai